2014
DOI: 10.9790/5736-0761104111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Density on Flame Characteristics of Some Tropical Timbers

Abstract: Timber has always played an influencing role in the lives of humans. At high temperature and in the presence of air, it burns or decomposes exothermically. The flame characteristics studied were the ignition time, flame duration, flame propagation rate and afterglow time. Wet and oven-dry densities, moisture content and porosity index of these timbers were also measured. The oven-dry density range was 0.256 0.008 g/cm 3 to 1.111 0.039 g/cm 3 in which most of the timbers were of medium density (0.400-0.750 g/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Contrary to expectation however, there was no straight forward relationship between density (whether ODD or SDD) and ignition time. Some scholars [32,33] had reported that as timber density increases, the ignition time increases. Figure 3 shows that ignition time increases and decreases intermittently as timber density increases.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to expectation however, there was no straight forward relationship between density (whether ODD or SDD) and ignition time. Some scholars [32,33] had reported that as timber density increases, the ignition time increases. Figure 3 shows that ignition time increases and decreases intermittently as timber density increases.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on flammability studies of some fire tolerant trees of the tropical rain forests and as well the effects of density and moisture content of woods on some flame properties and flame retardants on timbers abound [18][19][20]24]. It is surprising that little or no effort had been made to correlate the physical properties of woods with the major parameters of flammability of fire tolerant trees.…”
Section: Introductionmentioning
confidence: 99%